Extremely Low Frecuency (ELF) Electromagnetic Radiation Potential To Accelerate Fracture Splicing - Sudarti; Sri Septi Dyah Pratiwi (UNUSA Press, 2022)
The treatment process for healing fractures in the community is still mostly done through traditional methods, which are generally referred to as